Calamities : 21 stories of disasters that touched the world--with exercises for developing reading comprehension and critical thinking skills - Billings, Henry, 1941-; Billings, Melissa Stone (Lincolnwood, Ill. : Jamestown Publishers, 1952)
Nonfiction articles examining natural disasters and other catastrophic incidents (such as the Love Canal chemical dumping and the TWA Flight 800 crash). Each is followed by reading comprehension and critical thinking exercises.
"Levels F-H."
Keywords: Reading (Middle school); Reading (Elementary); Reading comprehension -- Problems, exercises, etc; Natural disasters